Precautions taken by nurses about the prevention of Hospital-Acquired Infections in Intensive Care Units - KIRTIL, İNCİ (PROFESSIONAL MEDICAL PUBLICATIONS, 2018)
Objective: To determine the precautions that nurses take for avoiding hospital-acquired infections in intensive care units of a State University Medical Faculty Hospital in Istanbul. Methods: The research data were collected by a questionnaire developed by the authors. The study was conducted in intensive care units of a medical faculty hospital of a state university in Istanbul province. 85 nurses working in different various intensive care units and providing informed consent participated in the study. Results: Intravenous catheterization, urinary catheterization, ventilator-associated infections and surgical site infections were assessed. The questionnaire was scored by applying a conversion of 100 to the total scores obtained, with the highest score being 100 and lowest score being 0. The percentage of nurses that practised all of the approaches about preventing hospital-acquired infections was estimated to be 8.2% for catheter- related bloodstream infections, 67.1% for surgical site infections, 72.9% for catheter- associated urinary tract infections, 27.1% for ventilator-associated infections, 29.4% for isolation preventions and 62.5% for attempts related to sterilization/disinfection of the medical devices. Conclusion: It was seen that nurses use most of the effective measures in order to prevent hospital-acquired infections. The guidelines generated for intensive care units should be updated according to international standards as needed. These guidelines should be used effectively; the differences between intensive care units should be resolved and all nurses should be trained at certain intervals.
Keywords: Hospital-acquired infections; Intensive care nurse; Intensive care unit; VENTILATOR-ASSOCIATED PNEUMONIA